The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1017/s1368980010000261
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors associated with physical activity in Mexican adults

Abstract: Objective: To estimate the physical activity level among Mexican adults and to establish the sociodemographic variables that may be linked to active lifestyles. Design: Data from a cross-sectional survey were analysed. Physical activity was assessed using the short version of the International Physical Activity Questionnaire. The independent variables were sex, age, socio-economic status and size of town. Ordinal regression models were fitted to assess the association of physical activity levels with sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
1
8
3
Order By: Relevance
“…This study showed that, both in the urban site and overall, a higher proportion of single participants engaged in moderate-to-vigorous PA than those who were divorced or separated, and comparable results to these were reported by a study in Lebanon [44]. There are however also reports that show married people as being more active than the single people [45], and a study based in Nigeria found a positive association between being married and reaching sufficient PA levels [18]. However, in this study, being married was not a determinant factor for PA.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study showed that, both in the urban site and overall, a higher proportion of single participants engaged in moderate-to-vigorous PA than those who were divorced or separated, and comparable results to these were reported by a study in Lebanon [44]. There are however also reports that show married people as being more active than the single people [45], and a study based in Nigeria found a positive association between being married and reaching sufficient PA levels [18]. However, in this study, being married was not a determinant factor for PA.…”
Section: Discussionsupporting
confidence: 83%
“…This study was restricted to adults only, in two provinces of South Africa, and its findings may not be applicable countrywide. Finally, another limiting factor of this study was that PA was assessed with a version of IPAQ, a self-report measure associated with overestimation of PA levels [45]. Nevertheless, this study was based on a large cohort of urban and rural South Africans, primarily of African descent which was assessed using a standardized method for surveying risk factors for chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the participants (58.4%) performed insufficient PA (<150 min/week). The proportion of insufficient PA was higher than those proportions obtained in previous studies, which ranged from 30.2%–53.6% (Adeniyi, Idowu, Ogwumike, & Adeniyi, ; Jackson, Herber‐Gast, & Brown, ; Ortiz‐Hernádez & Ramos‐Ibáñez, ; Vagetti et al., ). Two reasons may explain the difference.…”
Section: Discussioncontrasting
confidence: 59%
“…What determines the level of physical activity -or rather their inactivity -among the Warszawa administration staff, technicians, and manual workers? Most reports have emphasized that the primary factor in changing a lifestyle is the place of residence [32] and awareness [33] (clearly connected with profession [34], income [35], and education [33]). The larger the city, the higher the activity.…”
Section: Discussionmentioning
confidence: 99%